Hotspot gene mutations and treatment response in myelodysplastic syndromes (MDS): predictive biomarkers and targeted strategies - Zhang, Rui; Kou, Wei; Wu, Tao; Zhou, Rui (Frontiers in Medicine, 2026)
The myelodysplastic syndromes (MDS) are clonal hematopoietic stem cell disorders characterized by cytopenia and a high risk of transformation to acute myeloid leukemia. In recent years, next-generation sequencing (NGS) has revealed common hotspot gene mutations in MDS, which are not only involved in disease progression, but also affect the responsiveness of different therapeutic strategies. Current research has revealed that ASXL1 mutations in MDS predict demethylating agents (HMAs) resistance, the combination of HMAs and Venetoclax (VEN) achieved an ORR of 87%. DNMT3A R882 mutations induce decitabine sensitivity via hemi-methylated enhancer trapping, and TET2 mutations enhance HMAs efficacy only in ASXL1 wild-type contexts (ORR 62.1% vs. co-mutated 19%). RUNX1 aberrations reduce chemotherapy responses (18.9% ORR in high-risk MDS) through DNA repair impairment, while BCOR/EZH2 loss drives cytarabine resistance. TP53 multi-hit lesions correlate with poor survival (OS <12 months) but respond to eprenetapopt-azacitidine (ORR 73%), and IDH1/2 inhibitors achieve durable remissions (ivosidenib ORR 83.3%, mOS 35.7 months). In this paper, we systematically illustrate the correlation between key gene mutations and the response to HMAs, chemotherapy and targeted therapies in MDS patients. This article summarizes the current evidence on gene mutations as predictive biomarkers and discusses the direction of individualized therapy.